Early Woodland Settlement and Land Use in Eastern New York - C. B. Rieth (Journal of Middle Atlantic Archaeology, 2008)
Excavations were recently conducted at the Schoharie Creek II site in Schoharie County, New York as part of a state and federally funded highway project. This work revealed stratified soils that produced artifacts dating to the Early Woodland period (ca. 1000 B.C. - A.D. 100). The data derived during this excavation provide insights into the settlement, and land use practices of these hunter-gatherer populations and their interaction with other groups in eastern New York. This information is important to understanding the prehistory of the Schoharie Valley and eastern New York.
Keywords: Early Woodland; New York; Schoharie Creek